The Role of Teacher Professionalism: The Importance of Education and Training in Skill Development - Wahyuni, Esti Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
A profession is a job or position that requires certain expertise. This means that a job or position called a profession cannot be held by just anyone, but must require preparation through special education and training The task of a teacher as a profession requires a teacher to develop professionalism according to the development of science and technology. Educating, teaching, and training students are the duties of teachers as a profession. There are many examples of professions, one example is teachers. Teacher is a profession, which means a position that requires special expertise as a teacher and cannot be done by just anyone outside the field of education. Teachers have rights and obligations that must be carried out. Teacher rights mean something that must be obtained after carrying out their obligations as a teacher. Meanwhile, teacher obligations are something that must be carried out by teachers in carrying out their profession.